BDE-47 exposure modulates cellular responses, oxidative stress and biotransformation related-genes in Mytilus galloprovincialis. Issue 107 (December 2020) - Messina, Concetta Maria; Espinosa Ruiz, Cristobal; Regoli, Francesco; Manuguerra, Simona; D'Agostino, Fabio; Avellone, Giuseppe; Sprovieri, Mario; Santulli, Andrea
Abstract: Polybrominated diphenyl ethers (PBDEs) are flame retardants, characterized by elevated stability in the marine environment, where are accumulated by organisms, inducing a wide panel of negative effects. In this study, some biochemical patterns related to toxicity, biotransformation and oxidative stress, were studied in the marine model system, Mytilus galloprovincialis, exposed to BDE-47. Mussels were fed with microalgae, previously treated with increasing concentrations of PBDEs (maximum dose 100 ng L-1 of BDE-47 per day). After 15 days of treatment, mussels were fed with the same diet without BDE-47, for additional 15 days. Gills and digestive glands were analyzed at T 0, at 15 and 30 days. Histopathological lesions were assessed in digestive glands of contaminated mussels, while expression of genes, related to cell cycle, multidrug resistance, oxidative stress and detoxification was evaluated on both gills and digestive glands. After 15 days, BDE-47 exposure significantly affected the cell activity in digestive gland and, at 30 days, only mussels exposed to the lower doses showed a certain recovery. Regarding the gene expression, both gills and digestive glands showed a significant down-regulation of the target genes at 15 days, although most of them were up-regulated at 30 days in digestive gland. The results on BDE-47 accumulation in mussels revealed a dose-dependent concentration in tissues, which remained elevated after further 15 days of depuration. This trend supports the responses of the biomarkers, indicating that exposure, at environmentally realistic concentrations of BDE-47, strongly modulates oxidative stress and related patterns of gene expression, suggesting concerns for long-term effect in the biota. Graphical abstract: Image 1 Highlights: Persistent pollutants accumulate in marine organisms. BDE-47 exposure affected the cell activity in digestive gland severally. BDE 47 may impair phase I/II biotransformation pathway detoxification mechanisms. BDE 47 produce oxidative stress and promotes cellular transformation.